The Question of Commissioning Fees in the us: A Composer’s Perspective - Wiprud, Theodore (Circuit)

(untitled) (Les Presses de l’Université de Montréal, 2016)
Active professional composers of concert and dramatic music continue to rely on commissions as an important source of income. Theodore Wiprud, a composer and senior arts administrator, examines how the sources and distribution of commissions has evolved in recent years in United States. A range of working composers discuss their experiences and how the nature of a given commission can affect everything from the creative process to a new work’s reception and performance opportunities.